2016
DOI: 10.1177/1350650116645025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of high-speed wheel/rail adhesion under interfacial liquid contamination using an elastic-plastic asperity contact model

Abstract: The objective of this paper is to investigate the high-speed wheel/rail adhesion under interfacial liquids contamination using a numerical model. This model considers the rheological property of interfacial liquids, elastic-plastic deformation of microasperities contact and the temperature across the film thickness. The pressure and the temperature fields can be obtained. The effects of train speed, surface roughness parameters, characteristic shear stress, and the slip ratio are investigated. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…This result is consistent with the flooded case. 16 It can be found that the temperatures in the cavitation areas are equal to the ambient temperature. That is because the liquid pressure in the cavitation area is zero.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is consistent with the flooded case. 16 It can be found that the temperatures in the cavitation areas are equal to the ambient temperature. That is because the liquid pressure in the cavitation area is zero.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noticed that the wheel/ rail contact area is divided into the pressurised and the starved regions, which is different from the flooded case. [13][14][15][16] The interfacial liquid is assumed to completely fill the gap in the flooded region (pressurised region). Nevertheless, the supply of the interfacial liquid in the inlet region and outlet regions, which are called as cavitation regions, cannot build the elastohydrodynamic lubrication (EHL).…”
Section: Numerical Modelmentioning
confidence: 99%
See 3 more Smart Citations